2015
DOI: 10.1515/fhort-2015-0015
|View full text |Cite
|
Sign up to set email alerts
|

Influence of superabsorbent polymers on the chemical composition of strawberry (Fragaria × ananassa Duch.) and biological activity in the soil

Abstract: By improving the air and water properties of soils, superabsorbent polymers can affect the increase and improvement of the quality of the yield of berry plants, including strawberries. Their presence in the soil has an influence on its biological activity as related to microorganisms. The aim of the research was to assess the influence of superabsorbent polymers added to the soil on the content of macroelements and sodium in the leaves and fruit of strawberry of the 'Elsanta' cultivar and changes in the number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
1
3
0
1
Order By: Relevance
“…These outcomes are consistent with reports on citrus trees (Vichiato et al, 2004 andEl-Enien &Moursi, 2019) and Egazy olive trees (El-Rhman et al, 2017). Similarly, Mikiciuk et al (2015) reported that polymer application increased nitrogen and potassium contents in strawberry leaves but did not affect phosphorus contents.…”
Section: Leaf Mineral Constituentssupporting
confidence: 91%
“…These outcomes are consistent with reports on citrus trees (Vichiato et al, 2004 andEl-Enien &Moursi, 2019) and Egazy olive trees (El-Rhman et al, 2017). Similarly, Mikiciuk et al (2015) reported that polymer application increased nitrogen and potassium contents in strawberry leaves but did not affect phosphorus contents.…”
Section: Leaf Mineral Constituentssupporting
confidence: 91%
“…These results agree with Naing and Lay (2017) who reported that the super absorbent polymers can absorb the nutrients needed by the plants and releases them gradually for the plants and thus prevent leaching of these elements. Also, Mikiciuk et al (2015) added that the application of hydrogel with two rates 1.8 and 3.6 g dm -3 of soil were increased significantly the amount of both nitrogen and potassium. Moreover, hydrogels also affect nutrients respectively uptake indirectly by increasing the moisture in the soil and subsequently ion mobility.…”
Section: -Yield Components Of Both Maize and Wheat Cropsmentioning
confidence: 99%
“…Moreover, germination process, plant growth, nutrients uptake by the plants and both water and fertilizers use efficiency were beneficially increased by mixing the plant pits in sandy soil with hydrogels (El-Hady and Wanas, 2006). According to many authors, superabsorbent polymers also have a beneficial effect on plant nutrient uptake, and increase the saturation of the sorption complex with bases, which prevents leaching losses of nutrients, thereby increasing the effectiveness of fertilization, and conduces to environmental protection (Guiwei and De Varennes, 2009, Kim et al, 2010and Mikiciuk et al, 2015. Bres and Weston (1993) studied that the effect of incorporated hydrogel amendments (Hydro source and Agri-gel, at rates of 1, 2, or 3 g L -1 ) to a soil less growth medium on ammonium, nitrate, and water retention and tomato (Lycopersicon esculentum Mill.)…”
Section: Introductionmentioning
confidence: 99%
“…Было показано, что синтетические полиакрилатные гидрогели не оказывают отрицательного влияния на микробиоту (84). Внесение в почву гидрогелей на основе рисовой соломы улучшало микробный состав почвы, при этом увеличивалась доля Azotobacter spp., а также бактерий, мобилизующих фосфат, грибов и актиномицетов (88), однако полимер на акриловой основе не влиял на содержание в почве актиномицетов и грибов (89). Также было показано, что добавление ПГГ на основе альгината положительно влияет на микробиоту почвы: внесение этого полимера в количестве 5 % приводило к увеличению обилия грибов, бактерий и актиномицетов соответственно на 28, 30 и 38 % (32).…”
Section: рис 1 направления применения полимерных гидрогелей в сельско...unclassified